Preparation of Anise and Thyme Lotion for Topical Use - R. Abed Al- Rahman, Issraa; J. Jawad, Fatima; H.Alkateeb, Ekbal; A. Abdulrasool, Alaa (Iraqi Journal of Pharmaceutical Sciences, 2017)
Anise and thyme crude extract were used to prepare a lotion for topical application due to their antimicrobial, germicidal and antifungal effects. Two formulas were prepared using the mentioned natural plants, formula 2 (selected lotion) was the most acceptable one which contained veegum and xanthan gum as suspending agents in addition to other exceipients providing it good properties with high physical stability because of its flocculating, pouring, resuspending easily with sedimentation volume (F) 0.96. In addition to unchangeable odor and color with expiration date of one year. While the Preliminary clinical study was done using this lotion on 10 patients with infecious viral skin diseases, it was found that this lotion was successful as a topical preparation for allergy and mostly chicken pox.Key words: Anise, Thyme, Crude Extract, Antimicrobial Effect.